ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN RENTABILITAS PADA COMMANDITAIRE VENOOTSCHAP (CV) AGRAPAMA CIPTAPRASADA PASER DI TANAH GROGOT - Yeni Rizkiya; Amir Hamzah; Erni Susanti (Paser Institute Of Accounting and Finance, 2023)
This study aims to determine the level of development of the ratio of Liquidity, Solvency, and Profitability at CV. Agrapama Ciptaprasada Paser is based on the financial reports for 2020, 2021, and 2022 to measure the company's financial performance. Based on the results of the analysis of the Liquidity Ratio at CV. Agrapama Ciptaprasada Paser, namely the Current Ratio in 2020 was 5.53 times, experiencing a decrease of 2.19 times in 2021 to 3.34 times. Then, the Quick Ratio in 2020 was 553%, decreased by 219% in 2021 to 334%. Based on the results of the Solvency Ratio analysis on CV. Agrapama Ciptaprasada Paser, namely the 2020 Debt to Asset Ratio of 16%, increased 12% in 2021 to 28%. The 2020 debt-to-equity ratio is 19%, increasing by 20% in 2021 to 39%. Based on the results of the analysis of the Profitability Ratio on the CV. Agrapama Ciptaprasada Paser's Net Profit Margin in 2020 was 12%; in 2021, it remained at 12% and decreased 2022 by 2% to 10%. Then Return on Investment (ROI) in 2020 was 147%; in 2021, it increased by 145% to 292%; and in 2022, it decreased by 79% to 213%. Then, the Return on Equity (ROE) in 2020 was 21%, increased in 2021 by 28% to 49%, and in 2022 decreased by 27% to 22%, according to the analysis of the financial statements of CV. Agrapama Ciptaprasada Paser, by using these ratios, researchers can provide conclusions and suggestions, namely to take more into account the use of capital to minimize idle funds, increase effectiveness in managing asset management, and be more efficient in managing one's capital.